Perceptions of organizational effectiveness in public hospitals: Insights from frontline healthcare workers in Ghana - Emmanuel Kumah; Dorothy Serwaa Boakye; Richard Boateng; Michael Afari Baidoo; Emmanuel Osei Tutu; Osman Ibrahim; Sandra Abakah; Eric Kwabena Asante Osei; Maxwell Derrick Nyame (SAGE Open Medicine)
Background: Organizational effectiveness is vital in public hospitals, especially in low- and middle-income countries, including Ghana, where healthcare delivery faces resource constraints and high disease burdens. This study evaluates the organizational effectiveness of public hospitals in Ghana from the perspective of frontline healthcare workers. Methods: A cross-sectional study was conducted in four public hospitals using a validated World Health Organization questionnaire. A total of 477 frontline healthcare workers participated, assessing the perceived gap between current effectiveness (“as-is”) and ideal expectations (“should-be”) across 15 items. Data were analyzed using descriptive statistics and paired Student’s t -tests. Results: Significant gaps were identified between current organizational effectiveness and ideal expectations. The mean score for current effectiveness was 2.75 ± 0.63, while the ideal state scored 5.20 ± 0.43, yielding a significant mean difference of 2.45 ± 0.58 ( p  = 0.001). Major gaps were noted in conflict management, support for continuous learning, and valuing individual contributions. Only 8.4% rated their organizations as “extremely effective,” with 31% indicating a need for significant improvement. Conclusion: The findings reveal substantial gaps between current effectiveness and expectations, emphasizing the need for urgent reforms in conflict resolution, staff development, and fostering a learning-oriented culture to enhance hospital effectiveness and healthcare delivery in Ghana.